Portrayal of animals and birds on the pillars of the Sitaleshwar Temple - Temples of India Project Team (Jio Institute, 2024)
The portrayal of animals and birds on the pillars of the Sitaleshwar Temple is remarkable. The half-medallion decoration on one of the pillars captures the image of a tranquil and innocent lion, sitting and relaxing.